Developer et réduire :

a = (3x-2)(3x+2)

b = (5+x)(1-2x)

c = (x-7)(4x-3)

2
a= (3x - 2) (3x + 2)
a = 9x² + 6x - 6x -4
a = 9x² - 4

b= (5 + x) (1 - 2x)
b= 5 - 10x +x - 2x²
b= -2x² -9x + 5

c= (x - 7) (4x -3)
c = 4x² -3x -28x +21
c = 4x² -31x +21

Réponses

2014-01-18T17:24:24+01:00


A= (3x - 2) (3x + 2)

A= 9x² + 6x - 6x - 4

A= 9x² - 4


B= (5 + x) (1 - 2x)

B= 5 - 10x + x - 2x²

B= -2x² - 9x + 5


C= (x - 7) (4x - 3)

C= 4x² - 3x - 28x + 21

C= 4x² - 31x + 21

2014-01-18T17:57:50+01:00
Bonsoir

a = (3x-2)(3x+2)
a = 9x² + 6x - 6x -4
9x² -4

b = (5+x)(1-2x)
b = 5 - 10x +x - 2x²
- 2x² - 9x +5

c = (x-7)(4x-3)

c  = 4x² -3x - 28x +21
4x² - 31x +21